Video-feedback intervention for promoting social engagement in children with neurodevelopmental disabilities - Montirosso, Rosario; Micheletti, Serena; Pisoni, Camilla; Mascheroni, Eleonora; Scarano, Elisa; Naboni, Cecilia; Rosa, Elisa; Castagna, Annalisa; Bonino, Margherita; Fazzi, Elisa; Orcesi, Simona (Frontiers in Psychology, 2025)
IntroductionChildren with neurodevelopmental disabilities (NDs) display several developmental impairments across various domains that impact parent–child interactions, emphasizing the need for effective early interventions. This multi-centric study aimed to evaluate the impact of video-feedback intervention (VFI) on enhancing maternal behavior (i.e., sensitivity) and socio-emotional skills (i.e., engagement and emotionality) in children with NDs during normal or stressful interactions (i.e., the Face-to-Face Still-Face, [FFSF]) paradigm.MethodsA single-cohort design with pre-(T0) and post-(T1) intervention assessment was used to evaluate 37 mother–child dyads from three units in Northern Italy. The children, aged between 6 and 24 months, had a diagnosis of ND, including psychomotor delay (n = 26) and cerebral palsy (n = 5). The VFI was administered over 6 weeks, with each session focusing on improving parents’ developmental supporting behaviors and enhancing the quality of parent–child interactions. Using the Global Rating Scale coding system (GRS), child behaviors (engagement and emotionality) and maternal behavior (sensitivity) were assessed during the FFSF.ResultsAnalyses of variance (ANOVA) indicated significant improvement post-intervention in child engagement in the Reunion episode, with an increase in mother-directed gaze communicative gestures and positive vocalization. A paired sample t-test revealed that the mother’s sensitivity significantly improves between T0 and T1 during the Reunion phase. Moreover, a higher increase in sensitive maternal behavior during the Reunion phase was associated with greater child engagement at T1 during the Reunion episode. No significant changes post-intervention were observed in the emotionality of the child.ConclusionThe VFI effectively enhanced socio-emotional skills and maternal sensitivity during parent–child interactions, particularly in recovering from interactive disruptions.